Bio-inorganic composites as repair mortar for heritage structures - Thirumalini, S.; Sekar, S. K.; Bhuvaneshwari, B.; Iyer, Nagesh R. (Journal of Structural Engineering, 2025)
The focus of the present study is to bring the technical skills involved in the preparation of bio-inorganic or traditional herbal lime mortar in field and standardizing the preparation of repair mortar under controlled conditions for restoration works for heritage and historical monuments. Vadakkunnathan temple in Kerala is one such built heritage and an asset reflecting the values and culture of India, wherein traditional herbal lime mortar was extensively used. The traditional preparations of lime mortar in the temple involves the usage of herbs namely Oonjalvalli, Pananchikaai, Kulamavu, Kadukai and Jaggery over centuries. Three types of mixes such as reference mix (LM–R) without herbal extract, HEX-F mix with all herbs without control in water to lime ratio, as followed in traditional practice and HEX–L mix with all herbs, but optimized water to lime ratio are considered in the present study. Mortar cubes of 50 mm size are cast for evaluation of compressive strength and found that HEX–L has shown the higher compressive strength. The reason behind the enhanced strength is discussed based on the role played by the herbal extracts towards carbonation and optimized water to lime ratio with proper grinding. Characterisation studies such as XRD and SEM are used to investigate the phases and morphology of the hydration products of all the mixes. Addition of herbs lead to the formation of Gismodine and Calcium Aluminum Hydrate, which is responsible for enhanced strength and durability. The results obtained from the characterisation studies are well correlated with the compressive strength of the mixes.